Religião e cultura local: estudo de dois grupos espíritas potiguares - Oliveira, Fábio Fidelis de (2009)
The subject of this research is the spiritual religious field, connected with the local cultural perspectives. Its basis is the analysis of two spiritual groups settled in Natal/RN: The Spiritual Group Evangelho no Lar and the Spiritual Center Garimpeiros da Luz . These two groups represent a point of convergence of several sectors of this religion, either through its insertion in the local sphere or in contact to nationally influent leaders, like the mediums Francisco Cândido Xavier and Divaldo Pereira Franco. Then, it aims to reach the potiguar singularities in their spiritualism approaches, looking for an analyses to possible connections between local values and themes from the spiritualism largely developed in Brazil. So, its objective is to act in the scope of influence, references, representations and adaptive practices in a local context, and they signalize special practices . The approaches until now developed refer only to the living of a Brazilian spiritualism, perfectly developed in contact with the catholic substrate, but there s still a gap about the local observation, with its peculiarities, which its research aims to disclosure. The option for a qualitative approach, in perfect relationship with the nature of the questions which were made was considered as an appropriate way to guide the study. To reach this, it will be made an ethnography of the studied groups, not only in the use of open interviews with its members but also in the contact and observation of its religious behavior, for example: meeting for studies of the doctrine, mediunic meetings, public lectures, helping the public in general. As results of this research we can point to the delimitation of local cultural references, which are undeniable, in relation to the identification of RN personalities who are considered coordinators or active spirits in the work performed by the groups. Thus, Auta de Souza, poetess and woman of great religiosity, Augusto Severo de Albuquerque Maranhão, martyr of the aeronautics, Father João Maria, object of popular devotion and Abdias Antônio de Oliveira, ex president of the Spiritual Federation of RN, present themselves as spiritual beings who lead the adaptability to the local context. In such a context, we have to point out the work of mediums, who, having a specific charisma, interacted with the groups in the establishment of these cultural bridges already made in their own contexts (national level), through the work equally possible to be locally reproduced. This and other facts, point out to perspectives of cultural circularity , including referring to a greater linking to sub layers in a true zone that converges and has circulation between an erudite spiritualism with another one, turned to the incorporation of local and popular elements